2003
DOI: 10.1046/j.1432-1033.2003.03559.x
|View full text |Cite
|
Sign up to set email alerts
|

Argininosuccinate synthetase from the urea cycle to the citrulline–NO cycle

Abstract: Argininosuccinate synthetase (ASS, EC 6.3.4.5) catalyses the condensation of citrulline and aspartate to form argininosuccinate, the immediate precursor of arginine. First identified in the liver as the limiting enzyme of the urea cycle, ASS is now recognized as a ubiquitous enzyme in mammalian tissues. Indeed, discovery of the citrulline–NO cycle has increased interest in this enzyme that was found to represent a potential limiting step in NO synthesis. Depending on arginine utilization, location and regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
241
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(245 citation statements)
references
References 193 publications
(251 reference statements)
2
241
0
2
Order By: Relevance
“…11 ASS is the rate-limiting enzyme of the citrulline-NO cycle that regulates the supply of L-arginine as a substrate for NOS. 6 We showed that Bj-PRO-10c administration results in augmented NO production in SHR brain tissues as well as in primary cultures of postnatal SHR brain neurons. Bj-PRO-10c-induced NO production in neuronal cells was abolished by pretreatment of cells with ASS and NOS inhibitors (data not shown).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…11 ASS is the rate-limiting enzyme of the citrulline-NO cycle that regulates the supply of L-arginine as a substrate for NOS. 6 We showed that Bj-PRO-10c administration results in augmented NO production in SHR brain tissues as well as in primary cultures of postnatal SHR brain neurons. Bj-PRO-10c-induced NO production in neuronal cells was abolished by pretreatment of cells with ASS and NOS inhibitors (data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…ASS is an ubiquitous enzyme that is expressed in all tissues, including the brain. 6 This enzyme catalyzes the conjugation reaction of citrulline with aspartate to generate argininosuccinate, which in turn is converted by argininosuccinate lyase into fumarate and L-arginine. L-arginine is cleaved into citrulline and NO, completing the cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), the key enzyme of arginine synthesis, we observed that the mechanism involved might depend on the cell type studied. Indeed, we previously reported that the glutamine-induced cell swelling was involved in hepatocytes because hypo-osmolarity totally mimicked the glutamine stimulating effect on the mRNA level (10); but this was not the case in Caco-2 cells, a human intestinal cell line (17). The present work was therefore begun to specify the molecular mechanism involved in the stimulating effect of glutamine on ASS gene expression in Caco-2 cells.…”
mentioning
confidence: 83%